Highways to Heaven : Infrastructure Determinants and Trends in Latin America and the Caribbean - Cerra, Valerie (IMF Working Papers; Working Paper ;, 2016)
Inadequate infrastructure has been widely viewed as a principal barrier to growth and development in Latin America and the Caribbean. This paper provides a comprehensive overview of infrastructure in the region and highlights key areas in which infrastructure networks can be enhanced. The public and private sectors play complementary roles in improving the infrastructure network. Therefore, it is critical to strengthen public investment management processes as well as the regulatory framework, including to ensure an appropriate mix of financing and funding for projects and to address environmental concerns.